2020
DOI: 10.7554/elife.59153
|View full text |Cite
|
Sign up to set email alerts
|

Underlying dyslipidemia postpartum in women with a recent GDM pregnancy who develop type 2 diabetes

Abstract: Approximately 35% of women with Gestational Diabetes (GDM) progress to Type2 Diabetes (T2D) within 10 years. However, links between GDM and T2D are not well understood. We used a well-characterised GDM prospective cohort of 1,035 women following up to 8 years postpartum. Lipidomics profiling covering >1000 lipids, was performed on fasting plasma samples from participants 6-9week postpartum (171 incident T2D vs. 179 controls). We discovered 311 lipids positively and 70 lipids negatively associated with T2D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…We identified downregulated sphingolipid metabolism as the major molecular pathway eclipsing upregulated fatty acid biosynthesis in the Hispanic cohort ( Figure 2 A). Our findings support a previously identified association between sphingolipids with T2D development ( Buschard et al., 2005 ; Khan et al., 2019b ; Lai et al., 2020 ). Experimentally, we show that downregulated sphingolipid metabolism in mice affected insulin sensitivity ( Figure 3 C) and caused pancreatic β cell dysfunction in both isolated islets and pancreatic β cells ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We identified downregulated sphingolipid metabolism as the major molecular pathway eclipsing upregulated fatty acid biosynthesis in the Hispanic cohort ( Figure 2 A). Our findings support a previously identified association between sphingolipids with T2D development ( Buschard et al., 2005 ; Khan et al., 2019b ; Lai et al., 2020 ). Experimentally, we show that downregulated sphingolipid metabolism in mice affected insulin sensitivity ( Figure 3 C) and caused pancreatic β cell dysfunction in both isolated islets and pancreatic β cells ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…This study intended to gain a better understanding of the early-stage T2D pathophysiology, excluding major confounding factors (i.e., race, age, BMI, sex, and blood glucose). To this end, we designed a 1:1 pair-matched (i.e., race, age, BMI, sex, and glucose tolerance) case-control study that mined metabolomic ( Allalou et al., 2016 ) and lipidomic ( Khan et al., 2019b ; Lai et al., 2020 ) datasets of the SWIFT cohort. We identified downregulated sphingolipid metabolism as the major molecular pathway eclipsing upregulated fatty acid biosynthesis in the Hispanic cohort ( Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for GDM are known to be affected by hormonal changes and genetic factors as well as environmental factors such as obesity, diet, and lack of exercise [1][2][3]5]. Among environmental factors, food has been reported as an important factor, and it has been suggested that the frequent consumption of carbohydrates composed of simple sugars or animal fats is closely related to diabetes [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…With its prevalence clearly growing worldwide-specifically in South Korea, it is also rising-the trend has been suggested to be due to an inflation in the average maternal age at childbirth and a problem resulting from a lack of exercise [4]. Although the risk factors for GDM are similar to those for type 2 diabetes, its onset is known to be affected by overweightness, lack of exercise, and environmental factors and eating habits [5]. In addition, GDM has been reported to cause various physiological negative effects in pregnancy and on the fetus such as prematurity and fetal macrosomia [3].…”
Section: Introductionmentioning
confidence: 99%
“…The lipidomics data was obtained from our recently published paper where the details of lipidomics analysis were described [36]…”
Section: Targeted Lipidomic Profiling and Data Pre-processingmentioning
confidence: 99%